2022
DOI: 10.3389/fpain.2022.943360
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of pain experience and changes in heart rate variability through music-imaginative pain treatment

Abstract: Music-imaginative Pain Treatment (MIPT) is a form of music therapy addressing pain experience and affective attitudes toward pain. It includes two self-composed music pieces: one dedicated to the pain experience (pain music, PM) and the other to healing imagination (healing music, HM). Our non-experimental study addresses patients with chronic somatoform pain disorders participating in MIPT. The goal is to gain insight into the direct effect mechanisms of MIPT by combining outcome measures on both the objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The long-term impact of MIPT on psychological and physiological well-being cannot be derived from this case report. Also the clinical study in which this patient was participating only gives initial indications of short-term effects ( 1 ). However our findings will later help to better explain treatment successes or failures in the context of a larger clinical study (RCT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term impact of MIPT on psychological and physiological well-being cannot be derived from this case report. Also the clinical study in which this patient was participating only gives initial indications of short-term effects ( 1 ). However our findings will later help to better explain treatment successes or failures in the context of a larger clinical study (RCT).…”
Section: Discussionmentioning
confidence: 99%
“…These questions are central in the single case study of Mrs S., who participated in a clinical study by Metzner et al (2022) (1) with patients suffering from a chronic pain disorder and undergoing psychosomatic inpatient treatment. Rather than presenting outcomes this multi-perspective analysis aims to gain a differentiated insight into the complex impact levels, and their interconnections, that come into effect in MIPT.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of variability is associated with stress, anxiety and/or chronic pain, and has been linked to dysregulated parasympathetic activity (Ellis and Thayer, 2010;Tracy et al, 2016;Ginsberg et al, 2022). Although some heterogeneity is evident, analysis of music-related studies that have measured HRV as well respiratory rate and other cardiovascular signs show that music-based interventions increase HRV and can -dependent to some extent on the type of music that is presented (Davis and Thaut, 1989;Knight and Rickard, 2001;Ooishi et al, 2017) -lower heart rate and blood pressure, all indicative of increased vagal tone and enhanced activity in the parasympathetic nervous system (Okada et al, 2009;Koelsch and Jäncke, 2015;Wang et al, 2020;Ginsberg et al, 2022;Metzner et al, 2022;Ting et al, 2022;Cao and Zhang, 2023;Park et al, 2023). These signs of re-balancing of the ANS are often associated with reduced pain perception and often accompanied by a reduction in the stress related hormone cortisol (McKinney, Antoni, et al, 1997a;Grape et al, 2003;Kreutz et al, 2004;Koelsch et al, 2011Koelsch et al, , 2016Ooishi et al, 2017;Fu et al, 2019).…”
Section: Autonomic Nervous Systemmentioning
confidence: 99%
“…A systematic review of mindfulness-based stress reduction (MBSR) compared to cognitive behavioral therapy (CBT) suggested MBSR could be applied within CBT or in addition to CBT for reducing pain severity, pain interference and psychological distress in chronic pain (Khoo et al, 2019). Other music therapybased programs involving, for example, cooperative music composition and interaction (Metzner et al, 2022), or a combination of exercise and musical agency (Fritz et al, 2018;Schneider et al, 2022), have also been reported to lessen anxiety and decrease the experience of chronic pain.…”
Section: Meditation and Mindfulnessmentioning
confidence: 99%
See 1 more Smart Citation